2015
DOI: 10.1038/ncomms8355
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic cell rounding and epithelial thinning regulate lumen growth and shape

Abstract: Many organ functions rely on epithelial cavities with particular shapes. Morphogenetic anomalies in these cavities lead to kidney, brain or inner ear diseases. Despite their relevance, the mechanisms regulating lumen dimensions are poorly understood. Here, we perform live imaging of zebrafish inner ear development and quantitatively analyse the dynamics of lumen growth in 3D. Using genetic, chemical and mechanical interferences, we identify two new morphogenetic mechanisms underlying anisotropic lumen growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 57 publications
(78 reference statements)
10
89
0
Order By: Relevance
“…Indeed, although strategies for chemical perturbation of cell division have been pursued for decades (36), the advent of mechanical approaches opens the door to studies of physical perturbation. Our approach expands the applicability of in vitro cell mechanics studies by providing a platform to understand how confinement forces can affect mitosis (8). Further studies could lead to novel concepts, for example, perturbing cell division with a combination of cortex-weakening agents and external force (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although strategies for chemical perturbation of cell division have been pursued for decades (36), the advent of mechanical approaches opens the door to studies of physical perturbation. Our approach expands the applicability of in vitro cell mechanics studies by providing a platform to understand how confinement forces can affect mitosis (8). Further studies could lead to novel concepts, for example, perturbing cell division with a combination of cortex-weakening agents and external force (37).…”
Section: Discussionmentioning
confidence: 99%
“…I n mitosis, eukaryotic cells down-regulate focal adhesions and increase their cortical tension and intracellular pressure, thereby generating force to round up against external impediments (1)(2)(3). Recent studies in the epithelium and epidermis of various organisms indicate that mitotic cell rounding is involved in tissue organization, development, and homeostasis (4)(5)(6)(7)(8). Abnormal mitotic cell shape can have adverse consequences for chromosome segregation and tissue growth (9), in some cases contributing to tumorigenesis (7).…”
mentioning
confidence: 99%
“…While this is also happening in the inner ear, we found that every epithelial cell also reduces its volume and changes its shape, thinning the epithelium. 4 This would result in a net redistribution of fluid from the cells to the lumen, a novel kind of fluid flow. This seems to be a general feature of lumen formation processes, as tissue thinning during lumen growth can be observed in many lumen-forming organs.…”
mentioning
confidence: 99%
“…The understanding of these shaping mechanisms in vivo is challenging, as most of these organs are large and located deep in the embryo, hindering their in vivo imaging and whole 3D lumen reconstruction. We recently tackled this issue by imaging in real time the dynamics of lumenogenesis in the zebrafish inner ear, 4 a small and rather superficially located organ. Not studied before, the zebrafish otic vesicle lumen displays an asymmetric shape that resembles a biaxial ellipsoid, with one long axis and 2 equally sized short axes ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation